2016
DOI: 10.1002/anie.201609009
|View full text |Cite
|
Sign up to set email alerts
|

Bis(Cyclic Alkyl Amino Carbene) Ruthenium Complexes: A Versatile, Highly Efficient Tool for Olefin Metathesis

Abstract: The state‐of‐the‐art in olefin metathesis is application of N‐heterocyclic carbene (NHC)‐containing ruthenium alkylidenes for the formation of internal C=C bonds and of cyclic alkyl amino carbene (CAAC)‐containing ruthenium benzylidenes in the production of terminal olefins. A straightforward synthesis of bis(CAAC)Ru indenylidene complexes, which are highly effective in the formation of both terminal and internal C=C bonds at loadings as low as 1 ppm, is now reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 74 publications
2
110
1
3
Order By: Relevance
“…The approach to the synthesis of catalyst 5 was based on the conventional metalation route, where the free carbene L10,g enerated in situ from imidazolinium salt 7 and potassium tert-pentoxide in toluene, reacts with 2d (Umicore Grubbs Catalyst M1). However,a sw e, and others [17] learned, in the specific case of unsymmetricalc arbenes containingo ne smaller ando ne sufficiently bulkiers ubstituent, both phosphines of complex 2d undergo the ligand exchange reaction.T hus, insteado ft he expected 5,t he corresponding bis(uNHC)c omplex 8 was obtained as ar ed crystalline solid (62 %y ield). Unfortunately,a ll attempts (changingc onditions and reactant stoichiometry) to obtain the mono-uNHC catalyst 5 proved to be unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…The approach to the synthesis of catalyst 5 was based on the conventional metalation route, where the free carbene L10,g enerated in situ from imidazolinium salt 7 and potassium tert-pentoxide in toluene, reacts with 2d (Umicore Grubbs Catalyst M1). However,a sw e, and others [17] learned, in the specific case of unsymmetricalc arbenes containingo ne smaller ando ne sufficiently bulkiers ubstituent, both phosphines of complex 2d undergo the ligand exchange reaction.T hus, insteado ft he expected 5,t he corresponding bis(uNHC)c omplex 8 was obtained as ar ed crystalline solid (62 %y ield). Unfortunately,a ll attempts (changingc onditions and reactant stoichiometry) to obtain the mono-uNHC catalyst 5 proved to be unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason for this is that typically not the most advanced and stable ligands and/or the wrong, leaving arylidene groups (or analogs) were tagged for the purpose. It has recently been reported that Ru cyclic alkyl amino carbenes (CAAC), complexes exhibit superior olefin metathesis catalytic activity up to 315000 TON (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…In 2007, Bertrand together with Grubbs presented ruthenium pre‐catalysts with cyclic alkyl amino carbene (CAAC) ligands which are, to date, the best catalysts for the ethenolysis of oleic acid derivatives (Figure , L6‐C ) . More recently, Gawin et al., published series of bis(CAAC) complexes of enhanced selectivity . Also in 2007, Vougioukalakis and Grubbs published series of complexes bearing NHC ligands with fluorinated aryl moieties (Figure , L7‐A , C ) …”
Section: Introductionmentioning
confidence: 99%
“…[33,34] More recently,G awin et al,p ublished series of bis(CAAC) complexes of enhanced selectivity. [35] Also in 2007, Vougioukalakis and Grubbs published series of complexesb earing NHC ligandsw ith fluorinated aryl moieties (Figure 1, L7-A,C). [36] Similarly,C opØret group published in 2016 an uNHC Grubbstype complexb earing at rifluoromethyl group (Figure 1, L8-A).…”
Section: Introductionmentioning
confidence: 99%